Rehabilitation of degraded forests in lowland Kutai, East Kalimantan, Indonesia - Mori, T. (Center for International Forestry Research, 2001)
Undisturbed lowland primary forest in Kutai, East Kalimantan is usually distinguished by dominance of dipterocarp species in number of individuals, in basal area and by their emergence to more than 50 m in height. Forests in most lowland concession areas have been logged selectively and suffered from surface forest fires at least twice since 1970. Canopy height and dominance levels have decreased in proportion to extent and frequency of disturbances by logging and fires but the area of pioneer species has increased proportionally with degradation. Secondary forest species or pyrophytic trees have become dominant in all forest lands. Forest degradation in lowland Kutai is more serious than where forest has had only commercial logging. Rehabilitation methods should be tailored to existing forest structures; e.g., natural regeneration is most appropriate in forest dominated by primary species, and enrichment by patch planting in gap sites in forest with few mother trees. Macaranga forest or pyrophytic shrub forest should be artificially planted. This paper focuses on planting dipterocarps. Generally single species plantations of dipterocarps should be avoided, except for a few species e.g. Dryobalanops aromatica and Shorea robusta. When dipterocarps are used, the key to success for successful dipterocarp planting is light control and species choice. Light control should correspond to the light requirements of a species during its growing stages, so planting methods should reflect site conditions and growth characteristics of the species. These characteristics vary widely among dipterocarp species. Degraded forest types in East Kalimantan and rehabilitation measures for them are reviewed.